2011
DOI: 10.1128/jb.01477-10
|View full text |Cite
|
Sign up to set email alerts
|

Indole Transport across Escherichia coli Membranes

Abstract: Indole has many, diverse roles in bacterial signaling. It regulates the transition from exponential to stationary phase, it is involved in the control of plasmid stability, and it influences biofilm formation, virulence, and stress responses (including antibiotic resistance). Its role is not restricted to bacteria, and recently it has been shown to include mutually beneficial signaling between enteric bacteria and their mammalian hosts. In many respects indole behaves like the signaling component of a quorum-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 29 publications
2
77
0
1
Order By: Relevance
“…Indole induction of spy occurs primarily via BaeRS (24), induction of acrD and mdtABC via BaeRS and CpxARP, and induction of mdtEF via GadX (49). Indole has been reported to be excreted by the AcrEFTolC pump (50), although others have reported that acrEF is not required for indole export (51). Therefore, we tested the effects on spy expression of exposure to various indole concentrations in wild-type (M5402) and tolC mutant (M5403) cells.…”
Section: Resultsmentioning
confidence: 99%
“…Indole induction of spy occurs primarily via BaeRS (24), induction of acrD and mdtABC via BaeRS and CpxARP, and induction of mdtEF via GadX (49). Indole has been reported to be excreted by the AcrEFTolC pump (50), although others have reported that acrEF is not required for indole export (51). Therefore, we tested the effects on spy expression of exposure to various indole concentrations in wild-type (M5402) and tolC mutant (M5403) cells.…”
Section: Resultsmentioning
confidence: 99%
“…Indole is an intermediate product in tryptophan biosynthesis and is produced by the tryptophan degradation enzyme, tryptophanase (TnaA). Similar to AHLs, indole has been shown to be freely diffusible across bacterial membranes (14,26). While E. coli encodes TnaA and produces indole, S. Typhimurium does not.…”
mentioning
confidence: 99%
“…S1-S4. 1 To whom correspondence should be addressed: Dept. of Microbiology/Organismic Interactions, Auf der Morgenstelle 28, 72076 Tübingen, Germany.…”
mentioning
confidence: 99%
“…Efflux pumps are widespread among Gram-negative bacteria and mediate the secretion of various proteins and a wide variety of other molecules (1)(2)(3)(4)(5). They bridge the periplasm, allowing a one-step transfer of substrates beyond the outer membrane.…”
mentioning
confidence: 99%